Assessing Learning to Learn through Rubrics and Authentic Tasks - Capperucci, Davide (Studi sulla Formazione/Open Journal of Education, 2019)
The present paper outlines a research-training process carried out with a sample of primary and lower secondary school teachers aimed at assessing the key competence of citizenship learning to learn. For this purpose, an assessment model was developed called KC-ARCA Model (Key Competences - Assessment, Rubrics, Certification of Achievement Model) which was tested in an exploratory way within the schools involved in the research. The research-training group identified the competence of learning to learn as a sort of “core competence” able to develop learning and effective behaviours in several fields of action and study.